Filsafat Artificial Intelligence (AI) dan Kemanfaatan Untuk Mewujudkan Indonesia Yang Berperadaban - Babys, Rosa Anggelina; Babys, Salomon Andreas Mesak; Benu, Eni (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
AbstractArtificial intelligence, also called Artificial intelligence (AI) is a working system in computer technology that has been used in almost all digital technology. Artificial intelligence has the potential to change the dynamics of global society in positive and negative ways. This article intends to deepen understanding of AI philosophy as well as examine thoughts related to solutions for developing the civilization of the Indonesian nation and state in the current AI era. This research uses a descriptive qualitative analysis methodology with data collection techniques using philosophical methods and literature study. The results of this research emphasize that in the ontological dimension artificial intelligence (AI) is intelligence generated by computers because humans provide their intelligence to computers. Epistemologically, AI is a construction of various scientific approaches, and axiologically AI is a double-edged technology, because on the one hand AI can improve human qualities, but on the other hand it can dehumanize humans. The conclusion of this article is that AI must be used for purposes and interests that are capable of qualifying the life and civilization of humans and the Indonesian nation, therefore efforts are needed to develop national AI.Keyword: Filsafat, Artificial Inteligent, Peradaban